Conceptualizing coastal and maritime cultural heritage through communities of meaning and participation. (15th October 2021) - Ounanian, Kristen; van Tatenhove, Jan P.M.; Hansen, Carsten Jahn; Delaney, Alyne E.; Bohnstedt, Hanne; Azzopardi, Elaine; Flannery, Wesley; Toonen, Hilde; Kenter, Jasper O.; Ferguson, Laura; Kraan, Marloes; Macias, Jordi Vegas; et al.
Abstract: Coastal zones are historically rich with unique land/seascapes, tangible artifacts, and intangible cultural heritage. Coastal and maritime cultural heritage (CMCH) contends with various constraining conditions of the sea and shore—both geophysical and socially constructed—which we delineate to identify risks and threats to its sustainable management. In response to calls for the greater incorporation of CMCH in the name of regional development and blue growth, we propose a conceptual framework as a means to identify risks and sustainably manage CMCH. We develop the concepts of communities of meaning and communities of participation to address how CMCH is created and contested and identify key considerations for its management. Building on theories of space, place, and identity, the paper constructs communities of meaning in order to elaborate the various opportunities but also tensions in preserving CH and cultivating reliant enterprises as a part of wider regional development strategies. Working from this understanding of place and identity in degrees of inclusivity/exclusivity, the paper draws upon literature on deliberative and participatory governance, framed as communities of participation . These two concepts provide a vocabulary for managers to address calls for the promotion of CMCH and determine appropriate management strategies and governance based on policy objectives and the will of potentially multiple communities of meaning. Highlights: Conditions of seas and coasts impact the risks and resilience of cultural heritage. Coastal and maritime cultural heritage can divide and/or unite coastal communities. Communities of meaning comprise diverse actors with concern for cultural heritage. Cultural heritage governance must anticipate in-built tensions in its designation. Managers should address power in participatory and deliberative processes.